Geographical differences in the diet of Dissostichus mawsoni revealed by metabarcoding - Lee, Soo Rin; Choi, Seok-Gwan; Chung, Sangdeok; Kim, Doo Nam; Kang, Chang-Keun; Kim, Hyun-Woo (Frontiers in Marine Science, 2022)
The diet of the Antarctic toothfish (Dissostichus mawsoni) was analyzed using metabarcoding to determine whether spatiotemporal factors are related to its feeding ecology. A diet metabarcoding analysis was conducted for five years from 2016 to 2020 using 1,777 samples collected from two distantly located subareas, 88.3 and 58.4.1. Metabarcoding results revealed 105 prey haplotypes (29 families, 45 genera) in the stomach contents of D. mawsoni, which can serve as valuable genetic information for the accurate identification of piscine species inhabiting the Southern Ocean. Most of the stomach contents of D. mawsoni consisted of fish taxa, comprising 99.61% of read count, which is consistent with other studies indicating that D. mawsoni is piscivorous. The prey compositions were highly different between the two subareas (88.3 and 58.4.1) regardless of the year, indicating that the diet of D. mawsoni strongly reflects the fish assemblages in geographically different habitats. These results strongly suggest that the stomach contents are good ecological indicators for monitoring any changes in the marine ecosystem caused by either the fishery of D. mawsoni, the most voracious piscine predator in its habitat, or environmental changes. In addition, quantitative polymerase chain reaction results of the two most abundant Macrourus prey species of Antarctic toothfish, M. caml and M. whitsoni, showed that the distribution of these two species may be related to the dynamics of gyres, which flow along the Antarctic continent.